PJMHS 2022
DOI: 10.53350/pjmhs22167630
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CD3 Levels of Tumor Infiltrating Lymphocytes (TILs) in Various Grades of Oral Squamous Cell Carcinoma of Tertiary Care Hospitals of Peshawar

Abstract: Introduction:The diagnosis of oral squamous cell carcinoma occurs late in the disease. Poor prognosis of the patient is directly correlated with the occurrence of metastatic lesions. Lymphocytes that have invaded tumors significantly influence how well cancers respond to treatment. Objectives: The objective of the study was to compare the immunohistochemical expression of CD3 TILs receptor in various grades of oral squamous cell carcinoma. Materials and Methods: This study was a retrospective comparative cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…With mounting evidence, it is now known that ILCs react to environmental signals, release cytokines, and alter their type and function in inflammation and cancers [ 6 ]. While the contribution of innate and adaptive immunity as well as cytokines in OSCC is well-studied [ 9 ], data related to the inflammatory infiltrate in OSCC is scarce in Pakistan, with only a few studies reported in the literature [ 10 , 11 ]. It is therefore highly relevant to investigate ILCs, new players in the tumor-immune niche that may play dual roles in the OSCC tumor environment.…”
Section: Introductionmentioning
confidence: 99%
“…With mounting evidence, it is now known that ILCs react to environmental signals, release cytokines, and alter their type and function in inflammation and cancers [ 6 ]. While the contribution of innate and adaptive immunity as well as cytokines in OSCC is well-studied [ 9 ], data related to the inflammatory infiltrate in OSCC is scarce in Pakistan, with only a few studies reported in the literature [ 10 , 11 ]. It is therefore highly relevant to investigate ILCs, new players in the tumor-immune niche that may play dual roles in the OSCC tumor environment.…”
Section: Introductionmentioning
confidence: 99%